Ler e copiar, ouvir e registrar: um dicionário jesuítico como instrumento de aprendizado da língua geral na amazônia setecentista - PRUDENTE, Gabriel de Cássio Pinheiro (Universidade Federal do Pará, 2017)
The aim of this article is to understand how a dictionary, written by a German Jesuit in the eighteenth century, was used as a tool for learning the “língua geral” in the Amazon region. The analyzed document is understood as a part of Jesuit linguistic politics, in which the learning of languages was of fundamental importance for missionary activity. The concept of cultural mediation will be discussed because the dictionary is interpreted as an essential linguistic tool for the missionary, as a mediator, to aid his conversion work. Firstly, this article intends to give a general outline of Jesuit linguistic politics in Portuguese America. Secondly, the manuscript is placed in its historical context. Finally, indications found in the entries that clarify the process of dictionary making, the missionary trajectory of the author, and his learning of the Língua Geral are analyzed.